Preclinical evaluation of (99m)Tc(CO)(3)-aspartic-N-monoacetic acid, (99m)Tc(CO)(3)(ASMA), a new renal radiotracer with pharmacokinetic properties comparable to (131)I-OIH - Lipowska, Malgorzata (2012)
In an ongoing effort to develop a renal tracer with pharmacokinetic properties comparable to PAH and superior to those of both (99m)Tc-MAG3 and (131)I-OIH, we evaluated a new renal tricarbonyl radiotracer based on the aspartic-N-monoacetic acid ligand, (99m)Tc(CO)(3)(ASMA). The ASMA ligand features two carboxyl groups and an amine function for the coordination of the {(99m)Tc(CO)(3)}(+) core as well as a dangling carboxylate to facilitate rapid renal clearance. METHODS: rac-ASMA and L-ASMA were labeled with a (99m)Tc-tricarbonyl precursor and radiochemical purity of the labeled products was determined by HPLC. Using (131)I-OIH as an internal control, we evaluated biodistribution in normal rats with (99m)Tc(CO)(3)(ASMA) isomers and in rats with renal pedicle ligation with (99m)Tc(CO)(3)(rac-ASMA). Clearance studies were conducted in 4 additional rats. In vitro radiotracer stability was determined in PBS buffer pH 7.4 and in challenge studies with cysteine and histidine. (99m)Tc(CO)(3)(ASMA) metabolites in urine were analyzed by HPLC. RESULTS: Both (99m)Tc(CO)(3)(ASMA) preparations had > 99% radiochemical purity and were stable in PBS buffer pH 7.4 for 24 h. Challenge studies on both revealed no significant displacement of the ligand. In normal rats, % injected dose in urine at 10 and 60 min for both preparations averaged 103% and 106% that of (131)I-OIH, respectively. The renal clearances of (99m)Tc(CO)(3)(rac-ASMA) and (131)I-OIH were comparable (P = 0.48). The tracer was excreted unchanged in the urine, proving its in vivo stability. In pedicle-ligated rats, (99m)Tc(CO)(3)(rac-ASMA) had less excretion into the bowel (P < 0.05) and was better retained in the blood (P < 0.05) than (131)I-OIH. CONCLUSION: Both (99m)Tc(CO)(3)(ASMA) complexes have pharmacokinetic properties in rats comparable to or superior to those of (131)I-OIH, and human studies are warranted for their further evaluation.